Формування логічного мислення молодших школярів засобами позакласної роботи з інформатики - Остапйовська, Ірина; Ласкевич, Ольга (My University, 2018)
У статті досліджено ґенезу поняття «логічне мислення», проаналізовано основні особливості мислення людини та логічного мислення як його складової, досліджено особливості логічного мислення учнів початкової школи, його формування та розвиток. Зосереджено увагу на основних умовах, які сприяють розвитку логічного мислення учнів початкових класів. Актуалізовано поняття «позакласна робота», проаналізовано особливості позакласної роботи з інформатики у початкових класах. Виявлено та описано засоби позакласної роботи з інформатики, котрі сприятимуть формуванню та розвитку логічного мислення учнів початкових класів. Увагу зосереджено на використанні дидактичних ігор, елементів змагань та наочності (ребусів, кросвордів («хрестиківок»), криптограм). Наведено приклади їх використання і короткі методичні рекомендації, а також – можливі технології створення. Окреслено перспективи подальших досліджень. The genesis of the concept «logical thinking» was analyzed and basic features of human thinking and logical thinking as its component were investigated in the article. Features of the logical thinking of pupils of the primary school (the predominance of sensory, active analysis over abstract; insufficient formation of basic abilities of generalization; inability to distinguish characteristic features etc.), the characteristic features of its formation and development were investigated. Attention was focused on the basic conditions that contribute to the development of logical thinking of pupils of the primary school. The notion «extracurricular work» was actualized and defined, the features of extracurricular work in informatics in primary classes, its goals and tasks were analyzed, forms, methods and means, conditions conducive to the formation and development of logical thinking of pupils of the primary school were succinctly studied. The means of extracurricular work in informatics that will contribute to the formation and development of the logical thinking of pupils of the primary school were revealed and described. Attention is focused on the use of didactic games, elements of competitions and means of visibility (puzzles, crossword puzzles, cryptograms). Their content filling and use in the process of formation and development of logical thinking of pupils of the primary school in the process of extracurricular activities in informatics were described. Examples of use and brief methodological recommendations were given, and possible technologies of creation were proposed. Prospects for further research have been determined.
Keywords: мислення; логічне мислення; інформатика; позакласна робота з інформатики; початкова школа; молодші школярі; thinking; logical thinking; informatics; extracurricular work in informatics; primary school; pupils of the primary school